Modeling Political Participation Through Social Media Communication Effects: The Role Of Partisanship Among Young Voters In Pakistan - Tariq, Rehan (2022)
Political participation has always been considered a decisive component of politics that is essential for the strength of the political system in a democratic country. While research has established the positive impact of social media use on political participation and identified a rise in social media use in Pakistan, the problem of political disengagement among young voters raised severe concerns for the democratic system of the country. To address this problem, this study described social media communication’s effects for modelling political participation of young voters in Pakistan. The suggested model of this study, which is based on the O-S-R-O-R (Orientation-Stimuli-Orientation-Response) model of communication mediation, elucidates that the pathway from social media use to political participation is not simple but complex with specific mediating and moderating paths. Focusing on partisanship in the cultural context of Pakistan, this study applies Social Identity Theory (SIT) to explain the role of partisanship as a psychological disposition. A combination of SIT and O-S-R-O-R assisted in explaining different mediating and moderating paths. A survey was conducted to test the model on young voters (N= 410) in Pakistan aged between 18 to 29 years. A snowball sampling technique was used to select the study sample. The study findings advanced the communication mediation model as moderated mediation model of social media communication effects. The findings have policy implications for political institutions, political parties, and media organizations in Pakistan.